Modulation of neuromuscular excitability in response to acute noxious heat exposure has no additional effects on central and peripheral fatigability - Eimantas, Nerijus; Ivanove, Soneta; Baranauskiene, Neringa; Solianik, Rima; Brazaitis, Marius (Frontiers in Physiology, 2022)
Background: Whole-body hyperthermia (WBH) has an adverse effect on the nervous system and neurophysiological performance. In the present study, we examined whether short-duration whole-body immersion in 45 C water (HWI-45C), which produces a strong neural and temperature flux without inducing WBH, can increase or impair neurophysiological performance in humans. Methods: Fifteen men (aged 25±6 years) were enrolled in this study and participated in three experiments: (i) a brief (5-min) immersion of the whole body in 37 C water (WI-37C); (ii) a brief (5-min) HWI-45C; and (iii) a control trial in a thermoneutral condition at an ambient temperature of 24 C and 60% relative humidity. Before and after the immersions, neuromuscular function (electromyographic activity, reflexes, electrically and voluntary induced torque production, voluntary muscle activation level) were tested. To provoke central inhibition, the participants performed a sustained 2-min maximal voluntary contraction (MVC). Results: Thermophysiological strain was greater after HWI-45C than after WI-37C. Electrophysiological modulations of motor drive transmission and peripheral modulations of muscle contractility properties in response to HWI-45C seemed to have little effect on central activation of the exercising muscles and no effect on MVC production. Conclusions: Although exposure to acute noxious heat was effective in evoking neuromuscular excitability, the increases in core temperature (⁓0.2 C) and muscle temperature (⁓0.6 C) did not induce moderate or severe WBH. These changes did not seem to affect central structures; that is, there were no additional increases in central and/or peripheral fatigue during a sustained 2-min MVC.